2012
DOI: 10.1016/j.jmpt.2012.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Episodes and the Co-Occurrence of Chiropractic and Health Services Use Among Older Medicare Beneficiaries

Abstract: Objective The purpose of this study was to define and characterize episodes of chiropractic care among older Medicare beneficiaries, and evaluate the extent to which chiropractic services were used in tandem with conventional medicine. Methods Medicare Part B claims histories for 1991-2007 were linked to the nationally representative Survey on Assets and Health Dynamics among the Oldest Old (AHEAD) baseline (1993-1994) interviews to define episodes of chiropractic sensitive care using four approaches. Chirop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
2
30
1
Order By: Relevance
“…Informed by Liliedahl 42 and Weigel, 43 we identified patients who used 1 of 4 treatments during their episode: 1) only CMT; 2) conventional medical care followed by CMT; 3) CMT followed by conventional medical care; and 4) only conventional medical care.…”
Section: Methodsmentioning
confidence: 99%
“…Informed by Liliedahl 42 and Weigel, 43 we identified patients who used 1 of 4 treatments during their episode: 1) only CMT; 2) conventional medical care followed by CMT; 3) CMT followed by conventional medical care; and 4) only conventional medical care.…”
Section: Methodsmentioning
confidence: 99%
“…While a participant in the chiropractic treatment group could also use other non-chiropractic services for spine treatment, prior research has indicated that conditional upon choosing chiropractic for a particular care episode, the vast majority of services used during that episode are chiropractic. 27,33 …”
Section: Methodsmentioning
confidence: 99%
“…35–37 A provoking finding was that <10% of chiropractic users also use other medical services for the same episode of care. 38 There is some evidence that individuals become accustomed to seeking chiropractic care, possibly because of lower satisfaction with medical care. 37,39,40 Our findings may indicate that chiropractic care may be used as a substitute for (rather than in addition to) medical care.…”
Section: Discussionmentioning
confidence: 99%